Buya Hamka: Nationalism in Islamic Education in Indonesia - Muhammad Panji Gozali; Kurniawati; Nurzengky Ibrahim (Universitas Pendidikan Ganesha, 2022)
Strengthening and building the nation is a vital role of nationalism which is also a means of improving human living standards. Islamic education that is nationalistic can result in a pattern of Islamic education that deviates from Islamic teachings. This study aims to analyze the thought and relevance of the values ​​of Nationalism in Buya Hamka's Islamic education thought in Indonesia. This research method uses historical research methods. This research will be presented using descriptive-analytic history writing. The technique used to analyze the data is descriptive qualitative analysis. The results of this study indicate that a sense of nationalism can be obtained through Hamka's view of the world of education, especially in Islam. The principal value of nationalism through Islamic education is an effort to strengthen national values ​​as individual human beings who are part of a large society in the formation of the state. The meaning of Hamka's nationalism related to collective awareness in Islamic Education thought can be seen in the idiom recognition based on the first principle of Pancasila. The practice of religious values ​​will be able to fortify the nation's next generation from deviant acts.